Dissolved fulvic acids from a high arsenic aquifer shuttle electrons to enhance microbial iron reduction - Kulkarni, Harshad V.; Mladenov, Natalie; McKnight, Diane M.; Zheng, Yan; Kirk, Matthew F.; Nemergut, Diana R. (My University, 2017)
It was demonstrated more than two decades ago that microorganisms use humic substances, including fulvic acid (FA), as electron shuttles during iron (Fe) reduction in anaerobic soils and sediments. The relevance of this mechanism for the acceleration of Fe(III) reduction in arsenic-laden groundwater environments is gaining wider attention. Here we provide new evidence that dissolved FAs isolated from sediment-influenced surface water and groundwater in the Bengal Basin were capable of electron shuttling between Geobacter metallireducens and Fe(III). Moreover, all four Bangladesh sediment-derived dissolved FAs investigated in this study had higher electron accepting capacity (176 to 245 μmol/g) compared to aquatic FAs, such as Suwanee River Fulvic Acid (67 μmol/g). Our direct evidence that Bangladesh FAs are capable of intermediate electron transfer to Fe(III) supports other studies that implicate electron shuttling by sediment-derived aqueous humics to enhance Fe reduction and, in turn, As mobility. Overall, the finding of greater electron accepting capacity by dissolved FAs from groundwater and other sediment-influenced environments advances our understanding of mechanisms that control Fe reduction under conditions where electron transfer is the rate limiting step.
Citation: Harshad V. Kulkarni, Natalie Mladenov, Diane M. McKnight, Yan Zheng, Matthew F. Kirk, Diana R. Nemergut, Dissolved fulvic acids from a high arsenic aquifer shuttle electrons to enhance microbial iron reduction, In Science of The Total Environment, 615, 1390-1395, https://doi.org/10.1016/j.scitotenv.2017.09.164
Keywords: Iron; Arsenic; Organic matter; Bacteria; Fulvic acid; Groundwater